The Relationship Between Physical Condition with Suplex Throwing Ability of Wushu Sanda Athletes - Febriani, Anisa; Amin, Nur; Herdinata, Guntur Ratih Prestifa; Nilawati, Ika; Azura Kosni, Norlaila; Sutomo, Rio Noviansyach (AIBPM Publisher, 2025)
Wushu Sanda is a modern martial art that evolved from traditional Chinese martial arts. One of its core techniques, the suplex throw, requires explosive movement to lift and slam an opponent backward, which demands strength, balance, coordination, and proper technique. This study aimed to examine the relationship between physical condition and the ability to perform suplex throws among Wushu Sanda athletes. A quantitative correlational research design with a cross-sectional approach was employed. The sample consisted of 15 athletes selected using purposive sampling. Research instruments included mats, stopwatches, whistles, measuring scale boards, single bars, slam dummies, and hand dynamometers. Data were analyzed using univariate, bivariate, and multivariate methods with SPSS. The results revealed significant relationships between arm muscle strength (p = 0.01) and leg muscle power (p = 0.02) with suplex throwing ability. In contrast, no significant relationships were found for arm muscle endurance (p = 0.07), back muscle endurance (p = 0.38), and flexibility (p = 0.06). In conclusion, physical condition, particularly arm muscle strength and leg muscle power, was significantly associated with suplex throwing performance in Wushu Sanda athletes.